Description of a new species of Homonota (Reptilia, Squamata, Phyllodactylidae) from the central region of northern Paraguay - Cacciali Sosa, Pier (2018)
Homonota is a gecko distributed in central and southern South America with 12 species allocated in three groups. In this work, we performed molecular and morphological analyses of samples of Homonota from the central region of northern Paraguay, comparing the data with those of related species of the group: H. horrida and H. septentrionalis. We found strong molecular evidence (based on 16S, Cyt-b, and PRLR gene sequences) to distinguish this lineage as a new species. Morphological statistical analysis showed that females of the three species are different in metric characters (SVL and TL as the most contributing variables), whereas males are less differentiated. No robust differences were found in meristic characters. The most remarkable trait for the diagnosis of the new species is the presence of well-developed keeled tubercles on the sides of the neck, and lack of a white band (crescent-shaped) in the occipital area, which is present in H. horrida and H. septentrionalis. Nevertheless, in our sample, we found three specimens (one juvenile and two young adults) that exhibit the white occipital band. Thus, this character seems only reliable in adults of the new species. The new species is parapatric to H. septentrionalis, both inhabiting the Dry Chaco of Paraguay.